Autoimmune neurological syndromes associated limbic encephalitis and paraneoplastic cerebellar degeneration. (6th October 2016) - Ayas, Zeynep Özözen; Kotan, Dilcan; Aras, Yeşim Güzey
Highlights: This study conducted that 7 patients (5 limbic encephalitis, 2 paraneoplastic cerebellar degeneration) diagnosed with autoimmune neurological syndrome were retrospectively examined. All patients had abnormal brain imaging. Five patients had typical involvement of the bilateral mesiotemporal region on FLAIR and T2 sequences. Two patients had cerebellar degeneration. One of patientshad anti-GABAR B1 positivity. Tumors were detected in 2 patients while investigation for paraneoplasia screening. Early diagnosis and treatment are of paramount importance. We some results very different in literature. One of patients with LE presented first attack neuro-Behçet's syndrome. One of patients with LE first presented parotid adenoma. One of patients first presented nasopharenx adenocarcinoma. Abstract: Introduction: Autoimmune neurological syndrome is a group of disorders caused by cancer affecting nervous system by different immunological mechanisms. In this study, we aim to study the clinical symptoms, cerebrospinal fluid (CSF) findings, autoantibody tests, computed tomography (CT), magnetic resonance imaging (MRI) signs and treatment outcome of patients with autoimmune syndromes. Methods: In this study, 7 patients (4 male, 3 female) diagnosed with autoimmune neurological syndrome were retrospectively examined. Results: Five of patients were diagnosed with limbic encephalitis, two of them were paraneoplastic cerebellar degeneration. Confusion and seizure were the most seen symptoms. Two patients had psychiatric disturbances (28, 5%) followed by seizure. Headache was seen in 2 patients (% 28, 5), disartria in 1 patient (% 14, 2), and gait disorder in 2 patients (28, 5%). The duration of symptoms was 46 (3–150) days on average. CSF abnormalities were detected in 2 patients. CT and MRI of the brain was available in all patients. Five patients had involvement of mesiotemporal region, two patients had diffuse cerebellar atrophy. One of patients had anti-GABAR B1 positivity. Tumors were detected in 2 patients while investigation for paraneoplasia screening. Conclusion: Remission is only possible with the detection and treatment of the malignancy. Early diagnosis and treatment are of paramount importance.